2 - The Changing Face of Redress in South African Higher Education (1990-2005): Teboho Moja and Fred M. Hayward - Teboho Moja (Journal of Higher Education in Africa, 2005)
fhis study focuses on fifteen years of redress policies designed to redress past in qualities in South African higher education, particularly as reflected in funding. At tempts to reverse past injustices included measures to address racial inequities for tndividuals with limited access to higher education at one level, and at another fo used on institutional discrimination through unequal funding of institutions based on the racial groupings they were designated to serve. This led to policies to provide tnstitutional redress. Two periods are examined under two different Ministers ofEdu ation and provide information on different strategies, levels of commitment, and degrees of success. The pre-democracy period to 1994 shaped the debate around redress and acceptance of policies to establish equity in society. Political realities post-1994 reshaped the debate, institutional redress faltered, and the focus on indi vidual redress was prioritised with the establishment of a student financial aid scheme. The new funding formula implemented in 2005 includes some redress elements. It remains to be seen ifthey will be effective.